2017
DOI: 10.1002/ece3.2860
|View full text |Cite
|
Sign up to set email alerts
|

Postglacial recolonization shaped the genetic diversity of the winter moth (Operophtera brumata) in Europe

Abstract: Changes in climate conditions, particularly during the Quaternary climatic oscillations, have long been recognized to be important for shaping patterns of species diversity. For species residing in the western Palearctic, two commonly observed genetic patterns resulting from these cycles are as follows: (1) that the numbers and distributions of genetic lineages correspond with the use of geographically distinct glacial refugia and (2) that southern populations are generally more diverse than northern populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 88 publications
(154 reference statements)
3
28
1
Order By: Relevance
“…In that work, we genotyped field‐collected individuals from across Europe with 24 highly polymorhic microsatellie loci. In contrast to mtDNA sequence data that showed limited biogeographic structure between winter moth populations, we found evidence that individuals could be assigned to either an eastern or a western European genetic lineage, with a clear hybrid zone in central Europe (Andersen et al, ). Using approximate Bayesian computation (ABC) methods, we also hypothesized that the contemporary genetic diversity of European populations of this species was largely shaped by its retreat to refugia in the Iberian, Balkan, and Caucasus regions, and by hybridization between the Iberian and Balkan lineages postrecolonization.…”
Section: Introductioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In that work, we genotyped field‐collected individuals from across Europe with 24 highly polymorhic microsatellie loci. In contrast to mtDNA sequence data that showed limited biogeographic structure between winter moth populations, we found evidence that individuals could be assigned to either an eastern or a western European genetic lineage, with a clear hybrid zone in central Europe (Andersen et al, ). Using approximate Bayesian computation (ABC) methods, we also hypothesized that the contemporary genetic diversity of European populations of this species was largely shaped by its retreat to refugia in the Iberian, Balkan, and Caucasus regions, and by hybridization between the Iberian and Balkan lineages postrecolonization.…”
Section: Introductioncontrasting
confidence: 99%
“…We used the results from Andersen et al () to establish the relationships among the other European populations. Andersen et al () found strong support for the German lineage to be the result of admixture between the Spanish and Serbian lineages after the LGM. The authors were unable, however, to conclude whether the Serbian and Georgian lineages diverged before or after the divergence of the Spanish lineage, as these two scenarios received equivocal results.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations